Self-concept and its relations with cognitive and metacognitive factors regarding performance in specific domains of knowledge - Δερμιτζάκη, Ειρήνη; Ευκλείδη, Αναστασία (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF